In the loop: a social network approach to the willingness to communicate in the L2 (L2 WTC) - Gallagher, Hugh Colin (2012)
Despite the conceptual importance of investigating the social context(s) in which second-language (L2) learning and use take place, the decade-old “social turn” within the field of second-language acquisition (SLA) has yet to produce a “parsimonious system of valid and generalizable parameters to describe contextual characteristics” (Dörnyei, 2009a, p. 238). Accordingly, investigating social network structure has recently been suggested as a general approach to examining the link between person and environment (Beckner, et al., 2009). In the current thesis, I offer a network approach in which second-language (L2) learning and use is regarded both as purposeful and as constrained by one’s social relationships. Subsequently, in a first-of-its-kind study within SLA, I apply social network analysis – a diverse array of formally-defined measures of social position and other socio-structural features – to conceptualize and empirically test the relationship between social structure and the willingness to communicate in the L2 (L2 WTC), defined as the “readiness to enter into discourse at a particular time with a specific person or persons, using a L2” (MacIntyre, et al., 1998, p. 547). In a study of Chinese-speaking international students at a British university, trait-like L2 WTC is found to predict cross-cultural adjustment, suggesting the role of actively engaging with one’s new cultural surroundings in establishing an adaptive person-environment fit. Subsequently, in the first study to apply modern, graph-theoretic notions of social position to a network of L2 learners, a significant relationship is found between various notions of structural position among a network of international English-for-Academic-Purposes students, and dispositional L2 WTC. Overall, the results support L2 WTC as both purposeful and constrained, learned from one’s past interactions, yet pushing the individual to take advantage of opportunities to communicate in the L2. Implications, limitations, and future directions of a social network approach to L2 learning and use are also discussed.